Etiological and Clinical Profile of Seizures in Late Preterm and Term Neonates - A Retrospective Study in an Intramural Tertiary Care Centre - Venkatesh G; V Prakash; Mohd Sajjid; Elango (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Seizures represents the most distinctive signal of the neurological disease in the newborn period. Neonatal seizures are associated with unfavourable short and long term neurodevelopmental outcome. Objective: Our study was aimed at finding incidence, etiological factors, and clinical profile seizures in late preterm and term infants.Subject and Method:A retrospective study was conducted in an intramural tertiary care hospital, IOG, Chennai, India. Detailed antenatal, intrapartum history and baseline characteristics of both mother and infants, clinical details of seizures, investigations and neuroimaging details of 113 late preterm and term neonates with seizures data was collected from January 2018 to December 2018. Results:The incidence of seizures in late preterm and term neonates was 0.76% in our study. Hypoxic ischemic encephalopathy(HIE) was the commonest etiology(50.4%) followed by sepsis(24.8%). Majority of HIE neonates presented within 12 hrs of life (89%). Hypoglycemia(21.2%) was the commonest primary metabolic abnormality followed by hypocalcemia(9.7%). Clonic type was the most commonest type (82.3%) of seizure followed by subtle (73.5%) seizure. Conclusion:Hypoxic ischemic encephalopathy was the commonest etiology along with clonic seizures most commonest types. Hypoglycemia was the most commonest biochemical abnormality.